International polytechnic softball championship in Dungun - Borneo Post, (KK) (Borneo Post (KK), 2013)
DUNGUN: The Polytechnic Department is holding the fiveday 2013 International Ministry of Education Polytechnic Softball Championship starting yesterday at the Politeknik Sultan Mizan Zainal Abidin Dungun.The Polytechnic's public relations officer Zaharuddin Ab Ghani said the event involved teams from institutions of higher learning (IHL) nationwide and guest teams from Indonesia.He said the teams from Indonesia were Lakidende and Garuda for the men's category and Prembors for the women's. The local teams include those from Universiti Teknologi Tun Husein Onn, Putra Malaysia,. Universiti Malaya, Universiti Utara Malaysia and Universiti Perguruan Sultan Idris.